Surgical site infection surveillance among post caesarean section patients in a tertiary hospital, Nepal - Devi Kandel, Tika; Prasad Sharma G, Ram; Adhikari, Prativa; Uprety, Sunita (Journal of Chitwan Medical College, 2026)
Introduction: Surgical site infection (SSI) is a common complication in post-caesarean section patients. SSIs after caesarean section can increase maternal mortality and morbidity, lead to longer hospital stays, and impose an economic burden on the patient and their family. The aim of this study was to determine the incidence, timing of occurrence and the contributing factors for SSIs following caesarean at the tertiary care hospital. Method: This was a descriptive cross-sectional study conducted in Department of Obstetrics and Gynaecology Chitwan Medical College, Nepal, from Mar 2024 to Apr 2025, after taking ethical approval. Patients who developed post-caesarean section SSIs during their hospital stay or were admitted with for SSIs were included. Data were collected using a self-structured proforma including demographics, surgical and obstetric risk factors, signs and symptoms, and time of SSIs. The SPSS version 20 was used for descriptive n(%) analysis. Result: Out of 1,021 patients who underwent caesarean sections, 32(3.13%) developed SSIs, 24(75%) following emergency caesarean. Most cases, 19(59.37%) had surgery duration of >1 hour. Majority of SSIs, 25(78.12%), occurred after hospital discharge, and were superficial SSIs, 31(96.87%), 22(68.75%) among parity >2 and 21(65.62%) had previous caesarean, 4(12.5%) had gestational diabetes. Organism was identified in only 1(3.12%). Conclusion: In this study common risk factors for developing SSIs (3.13%) following caesarean sections were emergency procedures, surgery >1 hour, and multiparity. In most cases, SSIs are diagnosed after hospital discharge. Therefore, continuous surveillance and implementation of infection prevention measures is essential to reduce the incidence of SSIs